An Epidemiological Study on the Relationship between Drug Control Program and Patient Compliance in Elderly Patients with Hypertension. (30th July 2022) - Pu, Yuting; Wang, Xinye; Min, Bo; Sun, Zhibo
Abstract : Objective . To explore the relationship between medication control regimen and patient compliance in elderly hypertensive patients. Methods . A retrospective analysis of 1432 elderly hypertensive patients in our hospital from February 2020 to February 2021 was conducted. The general data of patients, the drug control regimen, the occurrence of drug side effects, and blood pressure control of patients during hospitalization and outpatient follow-up were statistically analyzed. Results . The first dose rate was higher in patients given a single dose during hospitalization than in patients followed up in outpatient clinics, and the discharge rate was lower than for single doses (P < 0.05 ). Patients had a lower first dose rate and a higher discharge rate for the two drug combinations during hospitalization compared to outpatient follow-up patients, while the first dose rate and discharge rate were significantly lower during hospitalization. Three drugs were administered (P < 0.05 ). A higher incidence of first-dose and discharge medication was observed in patients with four drug coadministration during hospitalization than in patients with outpatient follow-up. The incidence of angiotensin-converting enzyme inhibitors (dry cough) was higher and the incidence of diuretics (hypokalemia) was lower in patients during hospitalization compared with patients at outpatient follow-up (P < 0.05 ). Maximum systolic blood pressure and fluctuations in systolic and diastolic blood pressure were lower in well compliant patients than in poorly compliant patients (P < 0.05 ). First systolic, maximal systolic, first diastolic, maximal diastolic, systolic and diastolic fluctuations were higher in hospitalised patients than in patients with outpatient follow-up, regardless of treatment compliance (P < 0.05 ). Conclusion . Elderly hypertensive patients with outpatient follow-up had the best discharge medication compliance, patients during hospitalization showed good medication compliance, and patients with outpatient follow-up had poor medication compliance.